2019
DOI: 10.1038/s41598-019-49505-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between regular walking and periodontitis according to socioeconomic status: a cross-sectional study

Abstract: Physical activity reduces the risk and mortality risk of inflammatory diseases. This study aimed to examine the relationship between regular walking and periodontitis in a Korean representative sample of adults according to socioeconomic status. Data acquired by the Sixth Korea National Health and Nutrition Examination Survey in 2014 and 2015 were used. The survey was completed by 11,921 (5,175 males; 6,746 females) participants (≥19 years). Individuals without values on periodontitis were excluded, and 9,728 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…These results are consistent with the results of recent studies that have shown that physical activity is associated with a reduced prevalence of periodontitis and improved periodontal health of the population [ 26 28 ]. A study by Su-Jin Han et al [ 27 ] showed a significant association between regular walking and a lower prevalence of periodontitis. Merchant et al [ 28 ] confirmed these results.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the results of recent studies that have shown that physical activity is associated with a reduced prevalence of periodontitis and improved periodontal health of the population [ 26 28 ]. A study by Su-Jin Han et al [ 27 ] showed a significant association between regular walking and a lower prevalence of periodontitis. Merchant et al [ 28 ] confirmed these results.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity including walking was collected through a face-to-face interview. Regular walking defined participants who had walked at least 30 min at a time and ≥5 days a week during the last seven days [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…There is controversy regarding whether alcohol consumption is a protective factor against or a risk factor for periodontitis. However, low socioeconomic status has been associated with periodontitis [ 60 ] and dental caries [ 61 ]. Alcohol consumption and socioeconomic status may also affect oral microbiome composition, considering reports on oral microbes in periodontitis and dental caries.…”
Section: Factors Influencing the Oral Microbiomementioning
confidence: 99%